(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The COVID-19 pandemic's far-reaching effects extended far beyond the realm of public health, significantly impacting the global economy and, consequently, the banking sector. This research paper will explore the multifaceted ways in which COVID-19 disrupted banking systems worldwide. Borrowers and businesses face job losses, slowed sales, and declining profits as the virus continues to spread around the world. Banking customers are likely to start seeking financial relief. An obvious way that pandemics can impact financial systems is through their enormous economic costs. To managing the direct economic impact of the coronavirus, banks need to have a plan in place to protect employees and customers from its spread. Many banks are already starting to encourage remote working of some employees. In this paper, we are aimed to demonstrate an impact of pandemic covid-19 on the banking and financial sector. India’s coronavirus outbreak threatens a years-long clean up of its financial system, according to the Indian bank. Banks sit at the heart of the economy and provide funding to corporate and individuals. Their stability is crucial to keep the system up and running.